Combustion Characteristics of a Direct Injection Diesel Engine Fueled with Diesel-Ethanol-Palm Oil Methyl Ester Blends - Taib, Norhidayah Mat; Mansor, Mohd Radzi Abu; Wan Mahmood, Wan Mohd Faizal; Abdullah, Nik Rosli (International Journal of Engineering and Technology, 2018)
In this study, three different diesel-ethanol–palm oil methyl ester (PME) blends were used as fuel to investigate the combustion characteristics and engine emissions at the maximum engine speed of 1600 RPM. The characteristics were simulated by using Converge CFD software for a Yanmar single-cylinder direct-injection diesel engine parameter. 10%-40% of PME and 10%-40% ethanol were added to 50% diesel to make 100% blends and the results were compared to the combustion characteristics of 100% diesel fuel. The results indicated that the combustion characteristics of diesel-ethanol–PME blends have changed; a high percentage of ethanol have longer ignition delay and shortened with PME addition; a high percentage of PME in diesel-ethanol blends increased the in-cylinder pressure and heat release rate of the engine. Overall, compared to 100% diesel fuel, the diesel-ethanol-PME blends could lead to a reduction of both NOx and particulate emissions of the diesel engine except for the result of 40% of PME blends that has slightly higher NOx emission compared to diesel. With a high percentage of PME (E10B40) in the blends, the HC, CO emissions could decrease but slightly increase the NOx. Therefore, the implementation of PME in diesel-ethanol blends leads to better engine combustion and reduced the greenhouse emission from the engine.